Proceedings of the International Seminar on Safety and Security of Autonomous Vessels (ISSAV) and European STAMP Workshop and Conference (ESWC) 2019 - Hirdaris, Spyros (De Gruyter, 2020)
Aalto University hosted the 2nd edition of the International Seminar on Safety and Security of Autonomous Vessels (ISSAV) together with the 7th edition of the　European STAMP Workshop and Conference (ESWC). ISSAV promotes all aspects of maritime safety and security in the context of autonomous vessels. The seminar focuses on exchanging knowledge about key safety and security challenges and opportunities in the context of autonomous vessels and the autonomous maritime ecosystem. The ESWC focuses on applications and studies related to the Systems-Theoretic Accident Model and Processes (STAMP) which is a relatively new systems-thinking approach to engineering safer systems. The 2nd edition of the International Seminar on Safety and Security of Autonomous Vessels (ISSAV) and the 7th edition of the European STAMP Workshop and Conference (ESWC) took place 17-20 September 2019 in Helsinki, Finland. Scope - ISSAV Autonomous vessels have become a topic of high interest for the maritime transport industry. Recent progress in the development of technologies enabling autonomous systems has fostered the idea that autonomous vessels will soon be a reality. However, before the first autonomous vessel can be released into her actual context of operation, it is necessary to ensure that it is safe and secure.　The aim of ISSAV is to promote all aspects of maritime safety and security in the context of autonomous vessels. The seminar focuses on exchanging knowledge about key safety and security challenges and opportunities in the context of autonomous vessels and the autonomous maritime ecosystem. The seminar has a special emphasis on: The challenges in managing safety and security in the operation of autonomous vessels and the entire ecosystem of an autonomous ma